Socio-demographic correlates and prevalence of obesity among school children in Amritsar district, Punjab, India - Mehta, Amarveer S.; Devgun, Priyanka; Mehta, Harsheet; Monga, Shamim; Birgi, Harjot (International Journal Of Community Medicine And Public Health, 2020)
Background: Obesity, a key risk factor for the non-communicable diseases has become a serious health concern in developing nations. Present study aims at estimating the burden of overweight, obesity and socio-demographic co relates of obesity among school going children of Amritsar, Punjab, India. Methods: Estimate sample of 900 subjects were selected in the age group of 6 to 15 yrs. Nine schools (four rural and five urban) were taken at random in Amritsar district. The cross-sectional study was carried out in all the schools. Probability proportionate to size of population technique was used to decide the number of children to be studied from each school, class and then section. Systematic random sampling technique was used to select the children from each section. Pre-designed and pre-tested questionnaire was used to elicit the information on the subjects. Overweight and obesity was assessed by BMI for age. Appropriate statistical techniques were applied for analysis of data. Results: Above study showed that prevalence of overweight and obesity was 10.22% and 6.88% respectively. Among males 48 (52.2%) and 43 (69.4%) were overweight and obese, while females were 44 (47.8%) and 19 (30.6%) overweight and obese respectively. In socio demographic factors sex, residence, type of family, socioeconomic status was identified as significant risk factors. Conclusions: The study highlights the high burden of obesity in study population and the need for promoting healthy lifestyle changes focused on combating obesity.